Subject Review: On Different Image Encryption Algorithms - Zainab Mohammed Essa (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Due to the huge progresses in communication networks especially in the Internet network, it has led to exchange of many types of data via people. Data security has become a main worry. So, there is an growing importance in the use of encryption and decryption approaches. Chaotic encryption systems and AES (Advance Encryption Standard) and also many encryption techniques have been established to maintain data security. Many techniques were proposed to encrypt images... In this paper, we attempt to review and describe many methods used to encrypt images.
Keywords: Cryptography; Image Encryption; Advance Encryption Standard; Digital images